Synthesis and Biological Activity of Gold(I) N‐Heterocyclic Carbene Complexes with Long Aliphatic Side Chains. Issue 35 (7th November 2014) - Arcau, Julià; Andermark, Vincent; Rodrigues, Mafalda; Giannicchi, Ilaria; Pérez‐Garcia, Lluïsa; Ott, Ingo; Rodríguez, Laura
Abstract: Seven imidazolium salts have been synthesized from octadecylimidazole (Im18). These salts differ in the length of the alkyl chain length bound to the second nitrogen atom of the imidazolium ring [R = Me, Et, i Pr, Pr, Bu, decyl (Dec), octadecyl] and were used as synthetic precursors to obtain two series of gold(I) carbene complexes (AuNHC). The first series contains one labile ligand at the second coordinative position monocarbene, [AuCl(NHC)], and the second one comprises dicarbene complexes. Their biological activity has been evaluated with respect to two different cell lines, and thioredoxin reductase (TrxR) inhibition has also been evaluated for selected examples. Distinct effects have been observed for the imidazolium salts and monocarbene derivatives. Abstract : The syntheses of a series of imidazolium salts and mono‐ and dicarbene gold(I) complexes are reported together with a study of their cytotoxicity and inhibition of the thioredoxin reductase enzyme.